Stress and depression scales in aphasia: relation between the aphasia depression rating scale, stroke aphasia depression questionnaire-10, and the perceived stress scale. Issue 2 (17th February 2017) - Laures-Gore, Jacqueline S.; Farina, Matthew; Moore, Elliot; Russell, Scott
Abstract : Background: Assessment and diagnosis of post-stroke depression (PSD) among patients with aphasia presents unique challenges. A gold standard assessment of PSD among this population has yet to be identified. Objectives: The first aim was to investigate the association between two depression scales developed for assessing depressive symptoms among patients with aphasia. The second aim was to evaluate the relation between these scales and a measure of perceived stress. Method: Twenty-five (16 male; 9 female) individuals with history of left hemisphere cerebrovascular accident (CVA) were assessed for depression and perceived stress using the Stroke Aphasic Depression Questionnaire - 10 (SADQ-10), the Aphasia Depression Rating Scale (ADRS), and the Perceived Stress Scale (PSS). Results: SADQ-10 and ADRS ratings were strongly correlated with each other ( r  = 0.708, p  < 0.001). SADQ-10 ratings were strongly correlated with PSS ratings ( r  = 0.620, p  = 0.003), while ADRS ratings were moderately correlated ( r  = 0.492, p  = 0.027). Item analysis of each scale identified items which increased both inter-scale correlation and intra-scale consistency when excluded. Conclusions: The SADQ-10 and ADRS appear to be acceptable measures of depressive symptoms in aphasia patients. Measurements of perceived stress may also be an important factor in assessment of depressive symptoms.